The variability in qualitative determinants of Greek bitter vetch landraces - Lazaridi E.; Fragkiadaki V.; Hadjigeorgiou I.; Papadopoulos G.; Bebeli P.J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Bitter vetch (Vicia ervilia (L.) Willd.) is one of the eight Neolithic founder crops of the Fertile Crescent. Once extensively cultivated, nowadays is growing on a small scale around the Mediterranean Basin for its forage and grain, mainly as feed for ruminants. Efforts for conservation and quality determinants assessment have been intensified in the recent years, due to increased attention for underutilized crop species and their effect to global food security and the forthcoming climate change. Seed nutritional quality varied significantly (P<0.001), among forty-one Greek bitter vetch landraces. Ash content averaged at 2.66 g/100 g DM. Crude protein content ranged from 15.5 to 23.31 g/100 g DM and crude fiber from 2.79 to 4.05 g/100 g DM. NFEs also varied with an average of 62.03 g/100 g DM. Straw quality characteristics were also varied among six studied accessions. Crude protein and crude fiber contents ranged from 5.10 to 9.84 g/100 g DM and 32.06 to 43.06 g/100 g DM, respectively. ADF and NDF contents averaged at 39.02 g/100 g DM and 52.63 g/100 g DM, respectively. The seeds and straw of the Greek bitter vetch local populations studied revealed on average a nutritional value similar to that of collections studied elsewhere. However, local populations of interesting performance were identified which need further study.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)